2008
DOI: 10.1016/j.neulet.2008.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of trkB immunoreactive cells in the intermediolateral cell column of the rat spinal cord

Abstract: The objective of the present study was to characterize the trkB receptor immunoreactive (-ir) cells in the intermediolateral cell column (IML) of the upper thoracic spinal cord. Small trkB-ir cells (area =56.1 +/− 4.4 µm 2 ) observed in the IML showed characteristics of oligodendrocytes and were frequently observed in close apposition to choline acetyltransferase (ChAT)-ir cell bodies. Large trkB-ir cells (area =209.3 +/− 25.2 µm 2 ) showed immunoreactivity for the neuronal marker NeuN, indicating their neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…As described in previous studies (Skup et al, 2002; Macias et al, 2007; McCartney et al, 2008; Coulibaly and Isaacson, 2012), TrkB cells frequently were observed in close proximity to neuronal cell bodies in the IML and the ventral horn and thus were categorized as perineuronal. In order to determine the overlap of these cells with OL lineage cells markers, the expression of NG2, CC1 and/or TrkB by perineuronal cells and their association with ChAT immunoreactive (-ir) ventral horn neurons were analyzed.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…As described in previous studies (Skup et al, 2002; Macias et al, 2007; McCartney et al, 2008; Coulibaly and Isaacson, 2012), TrkB cells frequently were observed in close proximity to neuronal cell bodies in the IML and the ventral horn and thus were categorized as perineuronal. In order to determine the overlap of these cells with OL lineage cells markers, the expression of NG2, CC1 and/or TrkB by perineuronal cells and their association with ChAT immunoreactive (-ir) ventral horn neurons were analyzed.…”
Section: Resultssupporting
confidence: 56%
“…Subsequent studies from our laboratory confirmed that the TrkB cells were nonneuronal (McCartney et al, 2008), that many of the cells expressed CC1 (Coulibaly and Isaacson, 2012), and that they did not express markers for astrocytes or microglia (Skup et al 2002; Coulibaly, unpublished). Others have reported little colocalization of full length TrkB and GFAP in uninjured tissues, though reactive astrocytes can express full length TrkB following CNS injury (McKeon et al, 1997) and in models of multiple sclerosis (Colombo et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In an effort to determine which cell type in the OL lineage was responsible for the increased number of plaques per cell, double labeling of Cx32 with the OL markers TrkB [17,18], CC1 [19], or NG2 [20] was carried out. In a recent study from our lab, the majority of TrkB cells (>80%) were shown to colocalize CC1, indicating their mature phenotype [18], yet a proportion of TrkB cells may represent a separate pool of OL linage cells [18] and thus TrkB cells were considered separately.…”
Section: Resultsmentioning
confidence: 99%